FOCAL CORTICAL DYSPLASIA: ALGORITHM OF PREOPERATIVE EXAMINATION - S. O. Ayvazyan (Эпилепсия и пароксизмальные состояния)
In this paper we are discussing the issues of diagnosis, classification, features of preoperative evaluation and surgical treatment of focal cortical dysplasia in children. Particular attention is paid to the complexities of visualization of FCD, as well as the reasons of frequent poor postoperative outcomes in epilepsy associated with FCD.